Farmers' attitudes toward modern irrigation systems: a case study of the Republic of Yemen - Dabiah, Abdulaziz Thabet; Hasan Herab, Ahmed; Alotibi, Yahya S.; Shaman Alfridi, Jasser; Muddassir, Muhammad (Frontiers in Sustainable Food Systems, 2025)
This research aimed to study mango growers' attitudes toward modern irrigation systems in Al-Hudaydah governorate, Yemen. Data were collected from 323 mango growers using a simple random sampling technique with the help of a pre-tested paper-based questionnaire. The results showed that most mango growers had neutral attitudes toward modern irrigation systems. Moreover, the majority of mango growers were non-adopters. Growers' attitudes toward modern irrigation systems are determined by farmers' education, social participation, farm size, and adoption. Age, social participation, and adoption significantly positively correlated with growers' attitudes toward modern irrigation systems. Farm size showed a significant negative correlation with growers' attitudes toward modern irrigation systems. The study recommends that the Department of Agricultural Extension promote modern irrigation systems through the active involvement of various stakeholders. In addition, the government should make serious efforts to make modern irrigation technologies available in the market at a highly affordable cost. Overall, the positive attitudes and adoption of modern irrigation technologies by the growers would be advantageous for both the growers as well as the government, as these promising technologies have the potential to enhance agricultural productivity and reduce water scarcity.